Penentuan Prioritas Pemberian Respon Informasi Terhadap Nilai Laporan pada Helpdesk Service dengan Menggunakan Metode AHP - Erfan Erfan; Nuryuliani Nuryuliani (Universitas Indraprasta PGRI Jakarta, 2023)
Helpdesk Service at PT XYZ uses Zendesk media to communicate. This study aims to determine the priority of reports that need to be prioritized by the helpdesk service in communicating through Zendesk media. The process of determining the priority of Zendesk's media report features uses the AHP method in the weighting which is then tested with the Consistency Index and Consistency Ratio to find the priority percentage. It is later followed by the determination of helpdesk officers’ activities in supporting the report criteria that need to be prioritized in accordance with the company's vision in providing services. The test results can be used as operational standards and references for helpdesk officers in carrying out their duties. From the AHP weighting and CI & CR testing which are then converted to percentages, it is found that the percentage of the First Response report criteria is 49%, followed by Solved Ticket of 31% and Agent Touch of 20%. Based on these criteria, each helpdesk can pay attention to alternative steps in responding to activities.